Contracted Nose after Silicone Implantation: A New Classification System and Treatment Algorithm - Yong Kyu Kim; Seungho Shin; Nak Heon Kang; Joo Heon Kim (Archives of Plastic Surgery, 2017)
Background Silicone implants are frequently used in augmentation rhinoplasty in Asians. A common complication of silicone augmentation rhinoplasty is capsular contracture. This is similar to the capsular contracture after augmentation mammoplasty, but a classification for secondary contracture after augmentation rhinoplasty with silicone implants has not yet been established, and treatment algorithms by grade or severity have yet to be developed. Methods Photographs of 695 patients who underwent augmentation rhinoplasty with a silicone implant from May 2001 to May 2015 were analyzed. The mean observation period was 11.4 months. Of the patients, 81 were male and 614 were female, with a mean age of 35.9 years. Grades were assigned according to postoperative appearance. Grade I was a natural appearance, as if an implant had not been inserted. Grade II was an unnatural lateral margin of the implant. Clearly identifiable implant deviation was classified as grade III, and short nose deformation was grade IV. Results Grade I outcomes were found in 498 patients (71.7%), grade II outcomes in 101 (14.5%), grade III outcomes in 75 (10.8%), and grade IV outcomes in 21 patients (3.0%). Revision surgery was indicated for the 13.8% of all patients who had grade III or IV outcomes. Conclusions It is important to clinically classify the deformations due to secondary contracture after surgery and to establish treatment algorithms to improve scientific communication among rhinoplasty surgeons. In this study, we suggest guidelines for the clinical classification of secondary capsular contracture after augmentation rhinoplasty, and also propose a treatment algorithm.